2007
DOI: 10.1091/mbc.e07-02-0124
|View full text |Cite
|
Sign up to set email alerts
|

LEKTI Fragments Specifically Inhibit KLK5, KLK7, and KLK14 and Control Desquamation through a pH-dependent Interaction

Abstract: LEKTI is a 15-domain serine proteinase inhibitor whose defective expression underlies the severe autosomal recessive ichthyosiform skin disease, Netherton syndrome. Here, we show that LEKTI is produced as a precursor rapidly cleaved by furin, generating a variety of single or multidomain LEKTI fragments secreted in cultured keratinocytes and in the epidermis. The identity of these biological fragments (D1, D5, D6, D8 -D11, and D9 -D15) was inferred from biochemical analysis, using a panel of LEKTI antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
273
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(286 citation statements)
references
References 34 publications
5
273
1
7
Order By: Relevance
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2). In addition, several of the annotated TRMs (miR-125b, -138, and -376a) may target AGO2, an integral protein required for miRNA mediated repression (Leung et al 2006) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2). In addition, several of the annotated TRMs (miR-125b, -138, and -376a) may target AGO2, an integral protein required for miRNA mediated repression (Leung et al 2006) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…6 and 7). Although trigger factors of these cascades remain to be fully elucidated, skin desquamation may be stimulated by SC acidification and subsequent release of active initiator KLK5 (72). In seminal plasma, cascade activation is more likely triggered at the time of semen ejaculation due to an immediate drop in the available Zn 2ϩ , since this ion is spontaneously chelated by Sg proteins (41,(73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate epidermal barrier function in Tg KLK5 mice, we first examined the ability of the skin to prevent penetration of an external dye solution in a whole mount assay. Tg KLK5 neonates exhibited more patches of inhibits several members of the kallikrein related peptidase (KLK) serine protease family (KLK5, KLK7, and KLK14; Deraison et al, 2007;Fortugno et al, 2011). Additionally, LEKTI has been recently suggested to inhibit caspase 14 (Bennett et al, 2010).…”
Section: Klk5 Is Overexpressed In the Gr Of Tg-klk5 Micementioning
confidence: 99%
“…However, the significance of each protease implicated in the disease remains unclear. Loss of LEKTI leaves the activity of several proteases unopposed (Descargues et al, 2005;Deraison et al, 2007), many of which are capable of degrading desmosomes or filag grin, and stimulating inflammation. Protease activation cas cades present an additional layer of complexity by providing an avenue for proteases not targeted by LEKTI to be involved in NS, such as matriptase (Sales et al, 2010) and elastase 2 (ELA2; Bonnart et al, 2010).…”
Section: Klk5 Is Overexpressed In the Gr Of Tg-klk5 Micementioning
confidence: 99%